Fracture assessment of cracked clad pipelines with weld misalignment - Zhao, Haisheng (2018)
With increasing demand of recoverable corrosive hydrocarbons, metallurgically bonded double walled pipelines, referred to as clad pipelines, are widely used to transport the corrosive natural resources. The clad pipelines consist of a carbon steel outer pipe providing the load capacity and a corrosion resistant alloy liner protecting the carbon steel outer pipe from corrosion. The pipeline is constructed by joining one end of the pipe to the other end by girth welding process, and potential cracks are usually detected to initiate from the welding region. Furthermore, weld misalignment, centerline offset misalignment or angular misalignment, is also invariably introduced into the pipeline during the welding process, which further reduces the integrity of the pipes due to the introduction of local bending stress. Therefore, it’s crucial to investigate the fracture responses of cracked clad pipelines with weld misalignment. Although BS7910–Amendment 1 has proposed a fracture assessment equation for misaligned structures, the equation actually uses fracture parameters of aligned configurations to assess the corresponding parameters of misaligned ones based on superposition principle, resulting in an over-conservative prediction. Therefore, the fracture analysis for cracked configurations with weld misalignment needs to be investigated in detail. In this study, a finite element (FE) mesh generator is developed to serve for the cracked clad pipelines with weld misalignment, and a small-scale experimental test is carried out to verify the validity of the mesh generator. Based on the mesh generator, extensive 3-D FE analysis is performed to determine the stress intensity factors (SIFs) of aligned and misaligned welded joints. The corresponding SIF equations are proposed using multiple regression analysis, which consider the effect of weld misalignment on the SIFs directly, not by the superposition principle. Then, the fracture responses for oval-shaped clad pipelines with a surface crack are analyzed, and an equivalent J-estimation procedure is built up. Finally, engineering critical assessment is conducted to investigate the effect of weld misalignment on the cracked clad pipelines, and a fracture assessment framework covering the commonly used pipe configurations is established to predict the fracture parameters.